DESIGNING THE INFORMATION EDUCATIONAL ENVIRONMENT OF A MODERN HIGHER EDUCATIONAL INSTITUTION (Scientific Journal of the Dragomanov Ukrainian State University Series 2 Computer-Oriented Learning Systems, 2025)
The main direction of informatization of the institution of higher education of Ukraine in the conditions of distance learning is the formation of its modern information educational environment (IEE) to ensure a high level of access to education for students of higher education. The article outlines the main characteristics of the information and educational environment of a modern higher educational institution, in particular objectivity, didactic component, personal orientation, unity, integration, high technology, multimedia, virtuality, openness, pedagogy, mobility. The main stages of designing an information educational environment are presented, including: creating and implementing a web application of an automated management system, providing corporate accounts; filling in content on the educational institution's website; forming the structure and filling in the MOODLE system; integrating the web application, Google Calendar, corporate mail, and the MOODLE system; testing and debugging the proposed IЕЕ. Important components of the IЕЕ structure include: educational process management tools; educational process automation tools; content of the MOODLE system, aimed at forming the necessary general and professional competencies of students. The development of the project is outlined step-by-step, in particular, the purpose, tasks, content, uniqueness, expected results, personnel of the executors, stages of the project and its weaknesses are defined. The features of the project implementation to improve the quality of distance learning are presented. Weaknesses of the project have been identified, including: quite a large number of project participants, possible lack of motivation of the team due to the financial component, and reluctance of changes on the part of some teachers. For the effective implementation of the project, a strategy for working with stakeholders and a schedule of informational support for its implementation have been developed. Separately, a detailed description of the specification of project goals is provided, a hierarchy of the work structure is proposed, a Gantt chart is constructed, and further development prospects are outlined.
Keywords: project; MOODLE system; ACS application; Google Calendar